2009
DOI: 10.1051/forest/2008093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt on ROS homeostasis, lipid peroxidation and antioxidant mechanisms in Pinus pinaster suspension cells

Abstract: Abstract• In the Pinus genus, information on the effectiveness of oxidative defence mechanisms during exposure to salt is lacking. The effect of salt stress imposition on ROS homeostasis was investigated using maritime pine (Pinus pinaster Ait.) suspension cells as a model system.• Cells were maintained in MS-based medium, exposed to salt (50, 100 and 150 mM NaCl) and analysed for biomass production, evidencing a decreasing growth capacity. Use of 100 mM NaCl imposed severe salt stress without affecting cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Although salinity acclimation is considered a complex phenomenon, our results, combined with the previous reports (Uchida et al 2002), indicate that while salt stress could be detrimental to unacclimated plants, the previous application of a mild salt stress or low doses of H 2 O 2 could be responsible for reducing the deleterious effects of salinity on plant growth. It was well established that upon salinity stress, ROS levels can rise to excessive levels, with oxidative damage and cell death as a consequence (Azevedo et al 2009). Meanwhile, the tight regulation of ROS homeostasis by a complex network of ROS‐producing and ROS‐scavenging enzymes thus creates a baseline from which ROS spikes can act as a signal in different cellular processes (D’Autréaux and Toledano 2007; Mittler et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although salinity acclimation is considered a complex phenomenon, our results, combined with the previous reports (Uchida et al 2002), indicate that while salt stress could be detrimental to unacclimated plants, the previous application of a mild salt stress or low doses of H 2 O 2 could be responsible for reducing the deleterious effects of salinity on plant growth. It was well established that upon salinity stress, ROS levels can rise to excessive levels, with oxidative damage and cell death as a consequence (Azevedo et al 2009). Meanwhile, the tight regulation of ROS homeostasis by a complex network of ROS‐producing and ROS‐scavenging enzymes thus creates a baseline from which ROS spikes can act as a signal in different cellular processes (D’Autréaux and Toledano 2007; Mittler et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…If productions of hydroxyl radicals are not eliminated by any enzymatic and non-enzymatic defense mechanisms, overproduction of its ultimately leads to cell death (Desikan et al, 2005;Gill and Tuteja, 2010). As a result of the measurement of ROS using spectrophotometric, fluorescent dye probe and electron spin resonance (ESR) methods showed that various abiotic stress factors induced ROS formation in a wide range of plant species under in vitro conditions (Mohamed and Aly, 2004;Chakrabarty et al 2005;Gallego et al, 2005;Reddy and Raghavendra, 2006;Azevedo et al, 2009;Shehab et al, 2010;El-Beltagi et al, 2011 …”
Section: Introductionmentioning
confidence: 99%
“…The spectrophotometric measurement of TBARS or MDA generally used as oxidative stress biomarker and also to assess the degree of LPO. Many researchers reported that MDA content increased under several abiotic stress factors, which were induced in vitro conditions (Gallego et al, 2005;Erturk et al, 2007;Sivritepe et al, 2008;Shri et al, 2009;Azevedo et al, 2009;Cui et al, 2010;Shehab et al, 2010;El-Beltagi et al, 2011;Ghanaya et al, 2011). Another way to detect LPO is determination of Lipoxygenase (LOX; EC 1.13.11.12) activity.…”
Section: Introductionmentioning
confidence: 99%
“…Proline, soluble sugars, and soluble proteins are among those osmotic adjustment substances that are involved in subcellular structures and protein protection, energy supply, and antioxidation [36, 39, 40]. Song and Zheng [41] reported that the induced resistance in cotton seedlings against Fusarium wilt was related to the accumulation of proline in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that plant cell metabolism is manipulated by pathogen invasion, and, to survive these unfavorable conditions, plant cells accumulate higher level of osmotic adjustment substances [ 36 – 38 ]. Proline, soluble sugars, and soluble proteins are among those osmotic adjustment substances that are involved in subcellular structures and protein protection, energy supply, and antioxidation [ 36 , 39 , 40 ]. Song and Zheng [ 41 ] reported that the induced resistance in cotton seedlings against Fusarium wilt was related to the accumulation of proline in tissues.…”
Section: Discussionmentioning
confidence: 99%